Prabowo Subianto Sebelum dan Setelah menjadi Presiden (Analisis Dramaturgi pada Akun Instagram @prabowo) - Anshori, Muhammad Irfan; Titisari, Diah; Hayulinda Putri, Fitria; Ebang, Yohanes Berchemans (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Brawijaya, 2026)
The evolution of digital political communication has reshaped political branding on visual platforms like Instagram. This study uses Erving Goffman’s dramaturgy framework (front stage, back stage, impression management) to analyze political image shifts on Prabowo Subianto’s Instagram account (@prabowo) before and after his election as President of Indonesia in 2024, following three previous campaign losses and decades of a strictly military-focused image. Qualitative content and visual analysis of 812 pre-inauguration posts (October 2022–October 2024) and 47 post-inauguration posts reveal a clear shift: while his pre-presidential portrayal was overwhelmingly formal and military with minimal personal content (0.86%), his post-inauguration persona evolved into a hybrid of a